Accurate and efficient electronic structure calculations of semiconductor heterostructures using GGA-1/2 formalism - Kim, Seungchul (The Korean Physical Society, 2024)
We have demonstrated that the electronic structures of interfaces between semiconductors, dislocations in solids, and real-size quantum dots-which are challenging to simulate due to the large number of atoms involved-can be calculated in a cost-effective and accurate manner through the implementation of the GGA-1/2 formalism with a pseudo-atomic orbital (PAO) basis. The band offsets, particularly those of the valence bands, of four interfaces (InAs/AlSb, ZnSe/ZnS, GaN/SiO2, and anatase/rutile) and the light absorption spectrum of a ZnSe/ZnS core/shell quantum dot with a diameter of 4.9 nm and the redshift due to the shell were accurately reproduced. The combination of the PAO basis and half-occupation method represents a highly realistic approach to studying the electronic structure of semiconductor heterostructures, as it allows for the relaxation of constraints in the size of the structural model while accurately predicting band edge positions.